RFID-based indoor positioning of autonomous aid for disable people - Zakaria, Intan Suria (2013)
Nowadays, global positioning system (GPS) is widely used in localization area because it’s very capable and reliable. However, in indoor positioning, GPS capabilities are very limited since the satellite signals are typically strongly attenuated by walls and ceiling. Thus, this project introduced the concept which presents a self-localization of a mobile robot by fusing radio frequency identification (RFID) system and wireless communication using XBee module to be used in indoor environment. Two Xbee devices will be used to transfer data from the remote control unit to mobile robot. Aims of this project are to create a mobile robot that reacts to the remote control to go to the desired position as command. To meet the desired aim of this project, practical and compact design technique are emphasized in order to create a mobile robot and the remote control. Sixteen RFID cards are arranged in a fixed pattern on the floor. A unique code of each RFID card provides the position data to the mobile robot. An RFID reader act as antenna will be installed to read the card data on the below of the mobile robot. The user can make it come by easily pressing the remote control by informing the user location.